STUDI EPIDEMIOLOGI KEJADIAN TUBERKULOSIS DI KECAMATAN BABELAN KOTA - Ladyka Viola Aulia Armawan; Jumriah Nur (Klinikal Sains : Jurnal Analis Kesehatan, 2022)
Tuberculosis (TB) is a disease caused by the bacterium Mycobacterium tuberculosis. TB cases in West Java reaching 127,000 for 2019 . Spatial analysis using Geographic Information System (GIS) has been used in the health sector. GIS spatial analysis can identify the distribution and clustering of disease cases, and high-risk areas. Provides an overview of the distribution of age, gender and demographic patterns of residence based on the results of the BTA examination at the Babelan I Health Center. This type of research is a descriptive analytic study with a cross sectional design using GIS assistance to obtain a description of the spatial distribution of residential demographics. The research sample was all cases of Pulmonary TB registered with TB.03 in the TB Program unit at the Babelan I Health Center in January 2020 - December 2020. The results of the analysis of the age variable showed that of the 66 research respondents, most of them were elderly with an age range of 46 years to 65 years. by 43.9% (29 respondents), the sex variable of TB patients was mostly male with a percentage of 66.7% (44 respondents), bacteriological examination on AFB examination in cases of cough >2 weeks was found to be 83.1% (54 respondents), and the pattern of demographic distribution is mostly in Kebalen village at 40.9% (27 respondents). Keyword : Tuberculosis, BTA (+), Analisis Spasial, Risks Factor